PENERAPAN KONSEP STEM DALAM PENGEMBANGAN SISTEM INFORMASI PENGADAAN BARANG DAN PROGRAM REWARD POINT BERBASIS DESKTOP PADA PROSES BISNIS - Sri Wahyuni; Zulham Zulham; Amru Yasir (Universitas Dharmawangsa, 2025)
This research presents a desktop-based Goods Procurement Information System model that integrates an adaptive reward point mechanism as an instrument for controlling the process and user behavior in managing the purchase of household goods. Different from conventional procurement systems that focus on recording transactions, this system is designed with a STEM approach to convert operational activities into measurable performance indicators through a mathematical algorithm for awarding points. This approach allows the system to function not only as an administrative tool but as a data-driven work process regulation mechanism. The research method used was quasi-experimental with a comparative analysis before and after system implementation. Transaction data was analyzed to measure changes in procurement cycle times, recording error rates, and user compliance with the system flow. The results of the study showed that the implementation of the system resulted in a significant increase in process efficiency, a decrease in data errors and a consistent increase in user compliance levels. Reward point integration has proven effective in shifting user work patterns from reactive to proactive because every operational action has measurable performance consequences. This finding confirms that innovation in procurement information systems cannot be achieved solely through technical automation, but rather through the integration of system design, performance measurement, and algorithm-based incentive mechanisms. The proposed model provides conceptual and practical contributions as a new approach in the digital transformation of household goods purchasing management that is oriented towards efficiency, accountability and sustainable changes in work behavior.